Pengaruh Psychoeducational Parenting terhadap Kecemasan Orangtua yang Mempunyai Anak Penyandang Thalassemia Mayor - Hera Hijriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to study the effect of psychoeducational parenting on the anxiety of parents who have children with thalassemia major. This type of research is a quasi-experimental study using an interpretest and posttest with control group design approach. The results showed that there was an influence of psychoeducational parenting on the anxiety of parents who have children with thalassemia major (p value 0.006). Conclusion, there is the influence of psychoeducational parenting on the anxiety of parents who have children with thalassemia major. There is no influence of age, education, occupation, family income, and the presence of children with thalassemia in the family on the anxiety of parents who have children with thalassemia major. Keywords: Anxiety, Psychoeducational Parenting, Thalassemia